The Rumor of Missionaries Turning Gold in the Nanjing Church Case - XU, Yi (Journal of Research for Christianity in China (JRCC), 2025)
The doctrine of transmuting base metals into gold emerged as early as the Qin and Han dynasties and continued to evolve. During the late Ming period, Jesuit missionaries in China, though financially well-off yet uninvolved in productive labor, frequently became entangled in rumors surrounding this doctrine. Such rumors repeatedly provided ammunition for anti-Christian factions to attack them. This phenomenon was inextricably linked to both the folk tradition of seeking immortals and Taoist enlightenment and the image of missionaries in China. At its core, it stemmed from the differences and conflicts between traditional Chinese culture and Christian culture. This conflict found its most emblematic expression in the Nanjing church case. Confronted with the attacks of conservative literati like Shen Yue, Catholic literati and missionaries responded with documents such as the “Memorial on Distinguishing Learning” and the “Detailed Exposition.” Nevertheless, the Nanjing Incident dealt a severe blow to the Catholic mission in China.